Flock Use Among Bedouin in 'spontaneous' Settlements in The Negev Desert, Southern Israel. (1st January 2006) - Stavi, Ilan; Kressel, Gideon; Gutterman, Yitzchak; Degen, A. Allan
Abstract : Approximately a thousand Bedouin families living in unrecognised, scattered settlements in the Negev desert, Israel, raise sheep and goats even though this enterprise shows marginal profits and, sometimes, losses. The aim of this study was to examine the uses of flocks among Bedouin households. It emerged that the flocks were kept for status, preservation of social networks, source of income, employment, family cohesion and maintaining land claims.